2022
DOI: 10.34172/joddd.2022.026
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effects of different concentrations of simvastatin versus triple antibiotic paste on Enterococcus faecalis biofilms at different stages of development

Abstract: Background. This study assessed the antimicrobial effects of different concentrations of simvastatin versus triple antibiotic paste (TAP) on Enterococcus faecalis biofilms at different stages of development. Methods. In this in vitro study, 70 human single-rooted mature premolars were decoronated, instrumented, and autoclave-sterilized. Next, an E. faecalis suspension was prepared and inoculated into the canals to obtain 4- and 6-week biofilms. After ensuring biofilm formation, the samples in each group were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…SMV's anti-inflammatory, antibacterial, antioxidant, and bone/wound healing characteristics could account for the rapid pain alleviation that followed the application of the substance inside the canal [13]. 30]. The results of the study were found to be in favor of the current study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…SMV's anti-inflammatory, antibacterial, antioxidant, and bone/wound healing characteristics could account for the rapid pain alleviation that followed the application of the substance inside the canal [13]. 30]. The results of the study were found to be in favor of the current study.…”
Section: Discussionmentioning
confidence: 61%
“…Rahimi et al, in 2023, assessed the antimicrobial effects of different concentrations of SMV versus triple antibiotic paste (TAP) on E. faecalis biofilms and concluded that SMV has shown effective antimicrobial effects against E. faecalis [ 30 ]. The results of the study were found to be in favor of the current study.…”
Section: Discussionmentioning
confidence: 99%